(3GdUGgd hGdTGMLs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s
(3ChdgG (B:s
(3CSde Ydi GdMVQI GdYGdjI JSdje GdYGLR GdebUQ s
(3BNQgG (B:s
(3hdcf TjI Gdbde Ydi GdQCS dQCJ CfgG ddbdjd cedJ QSGdI GdUGgd hGdTGeL s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs